A Turkish adaptation of the revised post-event processing questionnaire - Baycan, Can. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Post-Event Processing (PEP) is described as repetitive and intrusive thinking on recent anxiety-provoking social interaction or performance situation. Models of social anxiety (e.g. Heimberg, Brozovich, & Rapee, 2014) suggest PEP is an important mechanism in maintenance and vulnerability for social anxiety. Post-Event Processing Questionnaire- Revised (PEPQ-R) was developed by McEvoy and Kingsep (2006) in order to assess this mechanism in individuals. Perfectionism as a transdiagnostic factor have been extensively studied concerning other psychological problems, such as depression and anxiety. Moreover, mediating role of different cognitive processes on the relationship between perfectionism and psychological distress have been examined. This study aims to adapt the PEPQ-R to Turkish and explore mediating role of PEPQ as a cognitive process on the relationship between perfectionism and other disorders. Data collected from 525 university students in Turkey through online survey tool. PEPQ-R with a battery of anxiety, depression, perfectionism and repetitive thinking measures were used in order to assess validity of PEPQ-R. Mediation analyses were conducted if PEPQ mediates the relationship between perfectionism and aspects of social anxiety and depression. Confirmatory factor analysis showed that the adaptation had adequate fit on the model, other analyses supported that PEPQ-R correlated with other measures in line with previous studies. These suggest adapted scale is a reliable and valid tool in assessment of PEP in Turkish individuals. Mediation analyses yield negligible results. Outcome of the analyses were discussed as limitations and future directions.
Keywords: Social phobia.